2012
DOI: 10.3389/fonc.2012.00032
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Capacity of IL-15-Stimulated Cytokine-Induced Killer Cells Against Human Acute Myeloid Leukemia and Rhabdomyosarcoma in Humanized Preclinical Mouse Models

Abstract: Allogeneic stem cell transplantation (allo-SCT) has become an important treatment modality for patients with high-risk acute myeloid leukemia (AML) and is also under investigation for soft tissue sarcomas. The therapeutic success is still limited by minimal residual disease (MRD) status ultimately leading to patients’ relapse. Adoptive donor lymphocyte infusions based on MRD status using IL-15-expanded cytokine-induced killer (CIK) cells may prevent relapse without causing graft-versus-host-disease (GvHD). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Trafficking of CIK cells is hard to investigate in cancer patients. One approach to further study the trafficking is to use various humanized mouse models [73]. In vivo trafficking can also be studied by tracking genetically engineered T cells upon infusion [74].…”
Section: Improving Cik Therapy For Epithelial Cancermentioning
confidence: 99%
“…Trafficking of CIK cells is hard to investigate in cancer patients. One approach to further study the trafficking is to use various humanized mouse models [73]. In vivo trafficking can also be studied by tracking genetically engineered T cells upon infusion [74].…”
Section: Improving Cik Therapy For Epithelial Cancermentioning
confidence: 99%
“…Enhancing CIK cells function in vivo through the administration of supportive cytokines therapy, such as IL-2, IL-12, and IFN-g, can improve the cytotoxicity but has been associated with substantial side effects. 10,11 The data showed that IL-15-stimulated CIK cells (IL-15-CIK cells) have an increased antitumor potential in vitro compared with IL-2-stimulated CIK cells (IL-2-CIK cells). 9 Conventional CIK cells are usually generated from peripheral blood mononuclear cells (PBMCs) of healthy donors or tumor patients, with IL-2, IFN-g, IL-1, and anti-CD3 monoclonal antibody.…”
mentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were isolated from peripheral blood by standard Ficoll separation, as previously described (5). Human peripheral blood samples were obtained with full informed consent from patients with HCC.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine-induced killer (CIK) cell therapy is currently one of the most commonly used immunotherapies (3). In order to improve the efficacy of CIK cell therapy, numerous strategies, including gene transfection (4), stimulation with certain growth factors (5), pretreatment with antitumor drugs (6), or combination with genetically modified dendritic cells (7), have been attempted in practice. However, a number of clinical trials of CIK cell therapies failed to demonstrate any noticeable improvement over other therapeutic regimens, neither in terms of HCC control rates nor long-term survival rates (8), suggesting that other factors, such as the environment where CIK cells are functioning, should also be considered for immunotherapies.…”
Section: Introductionmentioning
confidence: 99%